Theories of explanation - Pitt, Joseph C. (Oxford University Press, 1988)
Since the publication of Carl Hempel and Paul Oppenheim's ground-breaking work ""Studies in the Logic of Explanation, "" the theory of explanation has remained a major topic in the philosophy of science. This valuable collection provides readers with the opportunity to study some of the classicessays on the theory of explanation along with the best examples of the most recent work being done on the topic. In addition to the original Hempel and Oppenheim paper, the volume includes Scriven's critical reaction to it, Wilfrid Sellars's discussion of the problem of theoretical explanation, andpiece.